Mesenchymal stem cells from patients with chronic myeloid leukemia do not express BCR-ABL and have absence of chimerism after allogeneic bone marrow transplant - Carrara,R.C.V. (2007)
Bone marrow is a heterogeneous cell population which includes hematopoietic and mesenchymal progenitor cells. Dysregulated hematopoiesis occurs in chronic myelogenous leukemia (CML), being caused at least in part by abnormalities in the hematopoietic progenitors. However, the role of mesenchymal stem cells (MSCs) in CML has not been well characterized. The objectives of the present study were to observe the biological characteristics of MSCs from CML patients and to determine if MSCs originate in part from donors in CML patients after bone marrow transplantation (BMT). We analyzed MSCs from 5 untreated patients and from 3 CML patients after sex-mismatched allogeneic BMT. Flow cytometry analysis revealed the typical MSC phenotype and in vitro assays showed ability to differentiate into adipocytes and osteoblasts. Moreover, although some RT-PCR data were contradictory, combined fluorescence in situ hybridization analysis showed that MSCs from CML patients do not express the bcr-abl gene. Regarding MSCs of donor origin, although it is possible to detect Y target sequence by nested PCR, the low frequency (0.14 and 0.34%) of XY cells in 2 MSC CML patients by fluorescence in situ hybridization analysis suggests the presence of contaminant hematopoietic cells and the absence of host-derived MSCs in CML patients. Therefore, we conclude that MSCs from CML patients express the typical MSC phenotype, can differentiate into osteogenic and adipogenic lineages and do not express the bcr-abl gene. MSCs cannot be found in recipients 12 to 20 months after BMT. The influence of MSCs on the dysregulation of hematopoiesis in CML patients deserves further investigation.